A New Era for Educational Assessment - David Conley (Arizona State University, 2015)
In this article, David Conley focuses on how to assess meaningful learning in ways that promote student achievement while simultaneously meeting system accountability needs. The article draws upon research that supports the notion that a major shift in educational assessment is needed in order to encourage and evaluate the kind of learning that enables success in college and careers. Over the next several years, almost every state will either implement the Common Core State Standards or develop an alternative version of their own. The question worth posing is whether educational stakeholders should be satisfied with on- demand tests that measure only a subset of the standards, or will they demand something more like a system of assessments in which multiple measures result in deeper insight into student mastery of complex and cognitive challenging standards? This article presents a vision for a new system of assessments, one designed to support the kinds of ambitious teaching and learning that most parents say they want for their children. The article begins with a brief historical overview, describes where educational assessment appears to be headed in the near term, and then discusses some longer-term possibilities, concluding with a series of recommendations for how policymakers and practitioners can move toward a better model of assessment for teaching and learning.